Kunstwerken verworven door de Vlaamse gemeenschap in 1990-1991. (Brussel : Ministerie van de Vlaamse Gemeenschap, 1992)
Abramovic, Marina & Ulay ; De Backer, Dirk ; Banks, Nick ; Beekman, Jan ; van Bergen, Thé ; Berghe, Luk ; Bijl, Guillaume ; De Block, Luc ; Boltanski, Christian ; Van Braeckel, Malou ; Braeckman, Dirk ; Bruneau ; Brusselmans, Luc ; De Bruyckere, Berlinde ; Burssens, Jan ; Bytebier, Jean-Marie ; Van Caeckenbergh, Patrick ; Cane, Francky ; Castelein, Ingrid ; Claessens, Luc ; Claus, Filip ; Cole, Willem ; Colpaert, Erik ; Corillon, Patrick ; Crabeels, Cel ; Creten, Johan ; d'O, Honoré ; DC, Franky ; Decabooter, Lieven ; Dewaele, Daniel ; Dieleman, Piet ; Drybergh, Charles ; Dujourie, Lili ; Duyck, Johan ; Eerdekens, Fred ; Eyck, Peter Dan ; Eynde, Patrick Van Den ; Fabre, Jan ; Gees, Paul ; Gentils, Frans ; Geys, Jef ; Goethals, Marc ; De Groot, Arie ; Grossen, Luc ; Hamelrijck, Ado ; Hansen, Ben ; Hautman, Sigefride Bruna ; Hocks, Teun ; Hoflack, Mark ; Hoorne, Emiel ; Huyghe, Philip ; Van Innis, Benoît ; Van Isacker, Philip ; Jambers, Marc ; Janssens, Edwin ; Van Kerckhoven, Anne-Mie ; De Keyser, Bert ; Körmeling, John ; Kruger, Barbara ; Kuypers, Gerard ; Lambrecht, Jef ; Lebeau, Philippe ; Lohaus, Bernd ; Maet, Marc ; Van Malderen, Siegfried ; Mannaerts, Werner ; Mara, Pol ; Mees, Guy ; Michielsen, Bart ; Minne, Joris ; Mistiaen, Carlo ; Mol, Pieter Laurens ; Muller, Koen ; Noland, Cady ; Pacquée, Ria ; Parmentier, Johan ; De Perlinghi, Jérôme ; Peters, Willy ; Van Praet, Frans ; Rombouts, Guy ; Rombouts, Xavier ; Roobjee, Pjeroo ; De Rore, Joel ; Ruff, Thomas ; Sack, Stephen ; Sarmento, Julião ; De Sauter, Willy ; Schepers, Marc ; Van Severen, Dan ; Sherman, Cindy ; Slabbynck, Johan ; De Smet, Gery ; De Smet, Yves ; Van Sompel, Willy ; Sonck, Jacques ; De Spiegelaere, Patrick ; Swennen, Walter ; Swimberghe, Gilbert ; Temmerman, Jean-Pierre ; etc.
boek